Pediatric Oncology Patients and COVID-19: An Experience from the Tertiary COVID Care Facility in Eastern India: A Prospective Observational Study - Chowdhoury, Satyabrata Roy; Biswas, Himanshu Sekhar; Raut, Sumantra; Bhakta, Subhajit; Roy, Atanu; Banerjee, Swarnabindu; Nandi, Mousumi (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Pediatric oncology patients presumably are one of the most vulnerable groups during this ongoing coronavirus disease 2019 (COVID-19) pandemic. Not only they are immunocompromised thanks to their inherent disease and treatment regimens, but delay in initiation and maintenance of their treatment in this pandemic era also poses great concern. But the magnitude of this effect on pediatric oncology patients has not been well established due to paucity of data.Objective This study was proposed to assess clinicoepidemiological profile and outcome of the pediatric oncology patients who were infected with severe acute respiratory syndrome coronavirus 2 virus attending a COVID-19 care facility.Materials and Methods This was a prospective observational study conducted in a tertiary care hospital. All confirmed oncology patients up to age 12 years who either attended the oncology outpatient department or referred to COVID-19 care center from other cancer treatment facility were included in the study from May 2020 to September 2020. Data on demography, clinical features, investigations, treatment, complications, and outcome were collected. Descriptive statistical analysis was performed and common relevant investigations were compared between non-intensive care unit (ICU) and ICU group.Results The rate of COVID-19 positivity among the pediatric oncology patient attending oncology clinic of the hospital is 8.21%. Total 28 patients (12 from oncology clinic of our hospital and 16 from other hospitals referred to our COVID-19 unit) were included in our study. The most common malignancy was acute lymphoblastic leukemia (64.28%). The most common symptom was fever (64.28%). Oxygen therapy was needed for 42.85% patients. Eight patients required ICU admission (two required invasive ventilation and one required noninvasive ventilation). Positive C-reactive protein value was associated with severe disease requiring ICU admission. Mean delay in starting chemotherapy in newly diagnosed cases was 28.77 days (standard deviation = 9.67). One newly diagnosed patient expired due to preexisting disease.Conclusion Though vulnerable, most of the pediatric oncology patients suffered a mild COVID-19 infection without any significant COVID-19-related morbidity and mortality. There is a significant delay in starting specific oncology therapy, that is, chemotherapy as a result of the ongoing COVID-19 pandemic in newly diagnosed pediatric oncology patients, which can increase morbidities and mortality related to malignancy.
Keywords: COVID-19; pediatric oncology; pandemic; childhood malignancy